Reasons for adhesion and adherence to a remote case management program for fall prevention delivered to older adults: a qualitative study - Barros, Adão Porto (2025)
Objective: To analyze the reasons for participation and retention of older adults who suffered at least two falls in the previous year in an online multidisciplinary case management program for fall prevention, delivered remotely. Methods: Qualitative and observational study conducted in Brazil between 2021 and 2023, with 50 participants. Inclusion criteria were older adults with a history of at least two falls in the previous 12 months, the ability to walk, and access to resources for virtual communication. The 16-week intervention included case management on risk factors and supervised physical exercises. Sociodemographic data and answers to open ended questions about reasons for participation and retention were collected by video call and analyzed qualitatively using Bardin analysis. Results: Most participants were female (90%) and between 60 and 69 years of age (46%). The main reasons for participation were interest in the topic of falls (50.8%), the characteristics of the program being offered remotely and by a highly credible institution (16.9%), the provision of activities that promote quality of life and health (11.3%), and family encouragement (10.5%). Regarding retention, the characteristics of the program stood out in terms of the quality of the proposed model (41.2%), positive bond with researchers (33%), and contribution to research and the institution (8.2%). Conclusion: Reasons for participation and retention are related to the quality of the intrinsic characteristics of the program, which should be prioritized in order to increase the chances of greater implementation.